Preliminary evaluation of allograft from decellularized cadaveric Fascia lata - Lacerra, Carolina (2020)
The allograft from fascia lata has reconstructive capacity. It allows revascularization since the surrounding vessels of the receiving scaffold and induces migration, proliferation and adhesion of the cellular components of granulation tissue for integration to receiving tissue. Fascia lata grafts are used in various medical branches (traumatology and orthopedics, neurosurgery, ophthalmology, urogynecology and aesthetic medicine). These grafts are obtained by different processes and are preserved by different methods according to the manufacturer. The aim of this work was to obtain, at the Tissue Bank in Laboratorio de Hemoderivados de la Universidad Nacional de Córdoba, an allograft from decellularized cadaveric human fascia lata (freeze dried) and to evaluate cytotoxicity, microstructure and collagen content. The results showed that through obtaining and processing methods used here, we obtained an allograft with its histological structure preserved and no evidence of cytotoxicity. Likewise, collagen content was not affected by decellularizing procedure.